Glutathione transferase P silencing promotes neuronal differentiation of retinal R28 cells. Issue 9 (11th February 2019) - Sciarretta, Francesca; Fulci, Chiara; Palumbo, Camilla; Aquilano, Katia; Pastore, Anna; Iorio, Egidio; Lettieri‐Barbato, Daniele; Cicconi, Rosella; Minutolo, Antonella; Parravano, Mariacristina; Gilardi, Marta; Varano, Monica; et al.
Abstract: Glutathione transferases (GSTs) play an important role in retinal pathophysiology. Within this family, the GSTP isoform is known as an endogenous regulator of cell survival and proliferation pathways and of cellular responses to oxidative stress. In the present study we silenced GSTP in R28 cells, a retinal precursor cell line with markers of both glial and neuronal origin, and obtained stable clones which were viable and, unexpectedly, characterized by a more neuronal phenotype. The degree of neuronal differentiation was inversely correlated with GSTP residual expression levels. The clone with the lowest expression of GSTP showed metabolic reprogramming, a more favorable redox status and, despite its neuronal phenotype, a sensitivity to glutamate and 4‐hydroxynonenal toxicity comparable to that of control cells. Altogether, our evidence shows that near full depletion of GSTP in retinal precursor cells, triggers neuronal differentiation and prosurvival metabolic changes. Abstract : The enzyme glutathione transferase P (GSTP) protects cells from toxic compounds and oxidative stress. We silenced GSTP in R28 cells, a retinal precursor cell line and obtained viable clones unexpectedly characterized by a more neuronal phenotype. These clones provide evidence that reduction of GSTP levels can promote neuronal differentiation and that its near full depletion can trigger prosurvival metabolic changes.